Report of the special committee on registration of algal and plant names (including fossils) - Barkworth, Mary E. (2016)
The Special Committee on Registration of Algal and Plant Names (including fossils) was established at the XVIII International Botanical Congress (IBC) in Melbourne in 2011, its mandate being to consider what would be involved in registering algal and plant names (including fossils), using a procedure analogous to that for fungal names agreed upon in Melbourne and included as Art. 42 in the International Code of Nomenclature for algae, fungi, and plants. Because experience with voluntary registration was key to persuading mycologists of the advantages of mandatory registration, we began by asking institutions with a history of nomenclatural indexing to develop mechanisms that would permit registration. The task proved more difficult than anticipated, but considerable progress has been made, as is described in this report. It also became evident that the Nomenclature Section needs a structure that will allow ongoing discussion of registration and associated issues. Simultaneously with this report we are submitting four proposals that would provide such a structure.